(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2026)
The article is devoted to the scientific achievements of the famous florist and phytogeographer, Dr. A. Rehman (1840–1917), in the field of studying mosses, lichens, vascular plants. A brief biography of the scientist and information about his expeditions, of which there are about 40, are given. We have conventionally divided these expeditions into three periods: the period of Eurasian expeditions ((1859)1865–1874), the period of African expeditions (1875–1880), and the period of European expeditions (1881–1910). The result of these expeditions are numerous herbarium collections and separate thematic collections of A. Rehman, which are stored in a number of European, South African and North American herbaria. They contain many authentic specimens that served as the basis for the description of new species in the taxonomy by world-class botanists. For example, from A. Rehman’s African collections were described 29 taxa of vascular plants and 300 of bryophytes. The scientist’s significant contribution to the study of the taxonomic diversity of the genus Hieracium L. (Asteraceae) is noted: a rich herbarium material was collected and a number of works on this topic were published. Attention is drawn to the key role of A. Rehman in the publication of “Flora Polonica exsiccata”, which influenced the formation and development of systematic and floristic research in Ukraine and Poland. He explored vast territories belonging to different climatic zones with different plant formations and acquired extensive botanical knowledge about plants, which he embodied in his floristic and floristic-phytogeographical publications. The main scientific his works in the field of physical geography, systematics, taxonomy, floristics, phytogeography, geobotany and ethnography are presented and briefly analyzed. The article provides brief information about two collections of A. Rehman, which are stored separately in the Herbarium of the Ivan Franko National University of Lviv (LW): the collection of bryophytes from South Africa – 650 herbarium packages and the collection of the genus Hieracium L. from Europe – about 9,000 herbarium sheets.